2005
DOI: 10.5891/jafps.31.75
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Acetyl-CoA Synthetase in Ripened Bananas

Abstract: Acetyl-CoA synthetase (ACS) activity in fully ripened bananas was determined by HPLC. The ACS activity was higher for acetate as a substrate than for butyrate. The higher substrate specificity for acetate than for butyrate evidences that banana produces a great amount of acetate esters and a less amount of butyrate esters. The K. for MgCl2 for butyryl-CoA formation was 5-fold higher than that for acetyl-CoA formation. ACS activity was assayed in mitochondrial, microsomal, and cytosol fractions isolated from ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Many enzymes regarding the conversions between volatile alcohols, aldehydes/ketones, acids, and esters have been studied extensively in fruits and plants, and/or adapted from microorganism studies [8][9][10]. In banana fruit ripening, gene expression and enzyme activity of alcohol dehydrogenase (ADH, short and medium chains), which facilitates the interconversion between alcohols to aldehydes [11,12], acyl-CoA synthetase (ACS), which activates carboxylic acids to acyl-CoAs [13] thus can be used to biosynthesize esters, and alcohol acetyl transferase (AAT), which catalyzes ester biosynthesis, have been intensively studied (Figure 1) [14][15][16][17]. ALDH dehydrogenizes aldehydes to carboxylic acids in different plant tissues [1,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many enzymes regarding the conversions between volatile alcohols, aldehydes/ketones, acids, and esters have been studied extensively in fruits and plants, and/or adapted from microorganism studies [8][9][10]. In banana fruit ripening, gene expression and enzyme activity of alcohol dehydrogenase (ADH, short and medium chains), which facilitates the interconversion between alcohols to aldehydes [11,12], acyl-CoA synthetase (ACS), which activates carboxylic acids to acyl-CoAs [13] thus can be used to biosynthesize esters, and alcohol acetyl transferase (AAT), which catalyzes ester biosynthesis, have been intensively studied (Figure 1) [14][15][16][17]. ALDH dehydrogenizes aldehydes to carboxylic acids in different plant tissues [1,18].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the current study was to determine the enzyme which converts volatile straight and branched aldehydes to carboxylic acids, to identify their involvement in Beekwilder, Alvarez-Huerta et al [16] showed that when incubating petunia leaves with 3-methylbutanol vapor for 24 h, 3-methylbutyl 3-methylbutanoate was the dominant volatile, in addition to 3-methylbutanol in the headspace, indicating a strong dehydrogenization of 3-methylbutanol to 3-methylbutanal, further to 3-methylbutanoic acid, then passing through 3-methylbutanoyl-CoA, and finally synthesizing 3-methylbutyl 3methylbutanoate, catalyzed by ADH, ALDH, ACS, and AAT, respectively [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%